A diferenciação cognitiva progressiva com a idade - Resultados na Bateria de Provas de Raciocínio Diferencial - S. Almeida, Leandro (1989)
A comparison of scores on Battery of Differential Reasoning Tests (Almeida, 1985) by two different samples (secondary school students and army recruits) is done. Principal differences may be related with the specificity of the last sample (older, males, and intermediate level of schoolarization). Even correlation and factorial analyses of scores are in accord with theoretical and practical objectives of Battery (differential evaluation of reasoning ability by different kind of contents on each items’ subtest), one finds lower correlation coefficients and a lower effect of reasoning general factor. This aspect may be explained by the progressive differentiation theory and by the importance of extra-school experiences in that process.